STUDENTS’ PERCEPTION ON SPEAKING REGULATION IN ISLAMIC BOARDING SCHOOL - Wasilatul Bariroh; Dhurratul Hikmah; Iffatul Hafizoh Almaududy (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Islamic boarding schools are known for the institution that combines religious, academic, and social education. In recent years, many boarding schools have applied speaking regulations to strengthen students’ language skills through daily practice. Therefore, this study aimed to explore the perception of speaking regulation in Islamic boarding school regarding (1) how their perceptions of speaking regulation and (2) the factors influencing those perceptions of the speaking regulation. The research was conducted in Nurul Jadid Islamic Boarding School Probolinggo with 13 students from four language institutions at language zone of that Islamic Boarding School. A qualitative phenomenological approach was employed, with data collected through semi-structured interviews. This study analyze by using thematic analysis of Braun & Clarke. The findings indicate that, First, students’ perceptions of the speaking regulation developed through the stages of acceptance, understanding, and evaluation, where initial doubts gradually shifted into positive perception as they engaged with the regulation in their daily environment. Second, the findings show that students’ perceptions were influenced by various factors, including personal motivation, previous experience, the structure of the regulation itself, and supportive elements in their social and learning environment.